Great Human Potential Islamic Perspective - Mawi Asmawi; Alam Tarlam (MAQOLAT: Journal of Islamic Studies, 2023)
Humans are creatures created by God as the most perfect human beings both physically and form. Humans with that perfection have important potential within themselves as media to manage their lives and life in this universe. In addition, humans are more dominant and superior than other God's creatures because humans can think with reason that God has given as a tool to think about God's creations as well as the creator himself. The Qur'an gives appreciation to humans for their thinking abilities, but on the other hand, sometimes humans ignore their basic potential so that they feel that they are created only to be controlled by God. Hasn't God given logic to make humans think and make an effort in living life. Even though there are definitely choices that are offered by God. Allah created everything in this world in pairs, there are good and bad, black and white, high and low, rich and poor, male and female, heaven on earth, heaven hell and many more. If we think further, there are many choices in this life, namely by developing the self-potential that exists in the anatomy of our body as energy and great strength to fight and be competent in this life.